Analisis Minat Siswa Dalam Memilih Kompetensi Keahlian Dengan Metode Simple Additive Weighting (SAW) dan Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) - Pahira, Wulan; Anggai, Sajarwo; T., Thoyyibah (Jurnal Ilmu Komputer, 2023)
Every student who graduates from middle school plans to continue their education to the high school/vocational school level. Vocational Schools are schools that develop and prepare students to be able to work in their respective fields. There are 3 Skill Competencies, namely, 1) Institutional Financial Accounting, 2) Office Management and Business Services, and 3) Computer Network and Telecommunications Engineering. Of these 3 skill competencies, prospective students need to consider them in choosing skill competencies that suit their interests and talents, because after choosing skill competencies students will carry out education for approximately 3 years. In creating this skill competency selection system, the author used 2 methods, namely the SAW method and the MOORA method with 6 criteria: mathematics scores, ICT scores, English scores, math test scores, computer knowledge, and psychological tests. Based on the results of research using these two methods, the results obtained with preference values A1=0.782, A2=0.72, A3= 0.725, then the MOORA method obtained preference values A1=0.601, A2=0.53, and A3=0.527 with these two methods showing the same results as The highest preference value is A1. So that students enter the Institution's Financial Accounting Skills Competency. After testing the system using the SUS method, the percentage results were 75.9% (Acceptable) so that this system can be accepted and used effectively and efficiently in selecting skill competencies.